The Analysis of Determining Ampere, Voltage And Interval Time Parameters in The FCAW Welding Process to Minimize Deformation Using Taguchi Method - Rohmat, Rohmat (Universitas Trunojoyo Madura, 2024)
Welding is an important process in manufacturing work to produce strong and durable joints. In the welding process, there are various parameters that are considered and used, especially in the FCAW welding process. In this study, several types of FCAW welding machine parameters used are ampere, voltage, and interval time of welding. The purpose of this study is to obtain the best welding quality results by combining these parameters by finding a comparison of the three parameters to minimize one of the welding defects, namely deformation. The method used is using DOE. This method allows to identify the parameters that most affect the quality of the weld and determine the optimal settings for each parameter. From the results of data processing and analysis, it was found that the voltage parameter was the most influential on deformation. The combination of levels in the predetermined parameters is ampere at level 1 with a number of 150 A, voltage at level 1 with a number of 22 V, and interval time at 10 minutes. The experimental data model has been tested with regression analysis to obtain an R-squared of 79.43%, and the residual plot analysis follows a straight line, so that the model is normally distributed and the statistical test results are significant, meaning that the observation data represents real data.